IMPLEMENTASI ANT COLONY SYSTEM UNTUK PENCARIAN JALUR TERPENDEK (Kasus : Sistem Informasi Pariwisata Kota Kendari) - , La Ode Muhamad Tajidun,ST ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Information about tourist attraction is currently needed. On a tour, we commonly choose the shortest path to save money and reduce the cost. The shortest path issue generally can be divided into two methods, i.e., conventional method and heuristic method. Conventional method is rather unsuitable to be used to find the shortest path with huge amount of data. One of the heuristic methods is the ant colony system in which by using the method, searching for the shortest path can be performed in short time although huge data is involved. This research aims to design web based Geographic Information System using SVG (Scalable Vector Graphic), PHP, and MySql, and the Ant Colony System to generate route recommendation. Based on research results, ACS recommends the shortest path but it does not always give an optimal solution. By using this system, tourist will be able to obtain guidance from and to their destination.